Transduction of human MCP-3 by a parvoviral vector induces leukocyte infiltration and reduces growth of human cervical carcinoma cell xenografts - Wetzel, K.; Gröne, Hermann-Josef; Giese, Nathalia; Rommelaere, Jean; Dinsart, Christiane (The journal of gene medicine, 2001)
Background: The oncosuppressive properties of some autonomous parvoviruses such as H-1 virus, together with their low pathogenicity, make them attractive vectors for tumor-directed gene therapy. Indeed, it was recently shown that these viruses became endowed with an enhanced oncosuppressive activity after they had been engineered to deliver a recognized therapeutic transgene. This prompted us to use a parvoviral vector to analyse the antineoplastic capacity of MCP-3 (monocyte chemotactic protein-3), a CC chemokine which has a broad spectrum of target cells, and can thus be considered to be a promising candidate for cancer treatment. Methods: We explored the use of a parvovirus H-1-based vector encoding human MCP-3 for its antitumor potential on human cervical carcinoma cells. HeLa cells were infected in vitro with the recombinant virus hH1/MCP-3 at a low multiplicity [1 replication unit (RU)/cell] and we investigated the effect of parvovirus-mediated MCP-3 transduction on tumor formation and growth upon implantation of HeLa cells in nude mice. Results: Infection of HeLa cells with hH1/MCP-3 led to secretion of high levels of MCP-3 and to significant retardation of tumor growth in recipient mice, as compared with HeLa cells that were either buffer-treated or infected with a MCP-3-free vector. Tumors from hH1/MCP-3-infected HeLa cells were heavily infiltrated with activated macrophages and showed increased numbers of dendritic cells. In addition, activated natural killer (NK) cells were also recruited into MCP-3-transduced tumors. Conclusion: These observations indicate that parvovirus H-1-transduced MCP-3 is able to exert a significant antitumor activity which is mediated, at least in part, through macrophages and NK cells, under conditions in which activated T cells are lacking.
Gesehen am 15.02.2021